MENINGKATKAN KEPUASAN PELANGGAN MELALUI KUALITAS PELAYANAN, PERSEPSI HARGA DAN CUSTOMER EXPERIENCE DI GRAND CEMARA HOTEL JAKARTA - Hendra Rahmat Kurniawan; Bonifasius MH Nainggolan (LP2M Universitas Bina Bangsa, 2023)
The objective of this study is to investigate the impact of service quality, price perception, and customer experience on customer satisfaction. The research employed a purposive sampling method, resulting in a final sample size of 120 paricipants. The survey was conduscted among consumers of Grand Cemara Hotel Jakarta who had stayed at least twice, in accordance with the defined sampling approach. Data analysis was performed using multiple linear regression analysis, utilizing SPSS software version 25. Following an assessment of classical assumptions in multiple linear regression models, the findings indicated a positive and significant relationship between service quality and customer satisfaction at Grand Cemara Hotel Jakarta. Similar result were observed for the variables of price perception and customer experience. Theese three variables collectively exerted a significant influence on customer satisfaction. Among the three variable examined, price perception emerged as the most influential factor in determining satisfaction, followed by customer expeirence and service quality